Sự tâm lý bầy đàn, khả năng chống chọi, sự tỉnh thức, và ý định tiếp tục mua sắm trực tuyến sau đại dịch COVID-19 - Trịnh Thùy, Anh; Kiều Anh, Tài (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
Although the COVID-19 is continuing to spread around many parts of the world, researchers and practitioners have been increasingly interested in predicting post-pandemic consumer behaviour. This research aims to examine the impact of herd mentality, consumer resilience, and mindfulness on factors of post-adoption of online shopping: Confirmation of expectations, satisfaction, and continuance intention of online shopping. Data from a survey with Vietnamese consumers who have switched to or increased online shopping since the pandemic broke out was analysed using PLS-SEM. Results provided support for post-adoption factors: Confirmation of expectations influences satisfaction; and both confirmation of expectations and satisfaction drive continuance intention of online shopping. Findings also revealed discounting one's own information would lead to more imitating others, which in turn affects confirmation of expectations. Moreover, consumer resilience and mindfulness, and the interaction between these two concepts also have influences on confirmation of expectations. Theoretical contributions and managerial implications are also discussed in the paper.
Keywords: Herd mentality; Resilience; Mindfulness; Online shopping; Technology adoption; COVID-19